Problems and Parents' Efforts in Fulfilling Children's Rights during the Covid-19 Pandemic: Study in Ampelgading Village, Ampelgading District, Pemalang Regency - Siskha; Imahda Khoiri Furqon (Universitas Islam Tribakti Lirboyo Kediri, 2021)
This study discusses the fulfillment of children's rights, which is still being pursued in order to realize children's welfare. Efforts made by parents are the main foundation in fulfilling children's rights, because parents are the first party responsible for the protection and fulfillment of children's rights. Instead of being the party obliged to fulfill children's basic needs, parents with their limitations have the opportunity to exploit children with the excuse of helping parents. The Covid-19 pandemic has had a significant impact on various lines of life, including on the socio-economic life of the community. This research is a qualitative research conducted using observation and interview methods to parents who have school-age children in Ampelgading Village, Ampelgading District, Pemalang Regency. The results of this study indicate that various problems arose during the co-19 pandemic. One of them is the problem of fulfilling children's rights, be it the fulfillment of children's rights in the fields of education, health to the fulfillment of children's rights in care and nutrition. Efforts made by parents include working together with their spouses to restore the family economy so that children's rights can be fulfilled properly.